2000
DOI: 10.3168/jds.s0022-0302(00)74954-x
|View full text |Cite
|
Sign up to set email alerts
|

Transit of Radical Scavenging Activity of Milk Products Prepared by Maillard Reaction and Lactobacillus casei Strain Shirota Fermentation through the Hamster Intestine

Abstract: Oxidative stress in the colon is associated with the incidence of colon cancer. In situ, the suppression of oxidative stress in the colon would be an effective form of prevention of the cancer. In this study we investigated the transit of the radical scavenging activity of milk products through the hamster intestinal tract. Two types of skim milk products were prepared by Maillard reaction and then lactic acid fermentation. Heat treatment enhanced the radical scavenging activity for 2,2-diphenyl-1-picrylhydraz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…Both milk-kefir and soymilk-kefir displayed significantly greater scavenging activities than milk and soymilk, indicating that some components of the antioxidants present in the kefir grains were transferred to milk and soymilk during fermentation. In addition, the increased scavenging activity of fermented products may also be related to milk protein-and soybean protein-derived peptides (Chen, Muramoto, Yamauchi, & Nokihara, 1996;Nishino, Shibahara-Sone, Kikuchi-Hayakawa, & Ishikawa, 2000;Suetsuna et al, 2000). McCue and Shetty (2005) observed an increase of DPPH radical scavenging activity during yoghurt production from soymilk using Kefir cultures which may be due to the mobilization of phenolic compounds.…”
Section: The Frap and Dpph Methodsmentioning
confidence: 99%
“…Both milk-kefir and soymilk-kefir displayed significantly greater scavenging activities than milk and soymilk, indicating that some components of the antioxidants present in the kefir grains were transferred to milk and soymilk during fermentation. In addition, the increased scavenging activity of fermented products may also be related to milk protein-and soybean protein-derived peptides (Chen, Muramoto, Yamauchi, & Nokihara, 1996;Nishino, Shibahara-Sone, Kikuchi-Hayakawa, & Ishikawa, 2000;Suetsuna et al, 2000). McCue and Shetty (2005) observed an increase of DPPH radical scavenging activity during yoghurt production from soymilk using Kefir cultures which may be due to the mobilization of phenolic compounds.…”
Section: The Frap and Dpph Methodsmentioning
confidence: 99%
“…DPPH radical scavenging activity Antiradical activity against DPPH was determined by following the method of Nishino et al (2000) with slight modifications in preparation of samples and reaction volume. Stock solutions (1 mg/ml) of the peel extracts were prepared in ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…Based on ANOVA results, fermented cow, goat and camel milk had significantly higher antioxidant activity than their respective unfermented ones. Nishino et al (2000) reported that increased radical scavenging activity was due to the protein peptides present in the fermented milks. Radical scavenging activities of fermented milks suggest that they could be used as natural antioxidant supplement for improving human health.…”
Section: Antioxidant Activitymentioning
confidence: 99%